STUDY ON MECHANICAL PERFORMANCE AND FAILURE MECHANISM OF CARBON FIBER COMPOSITE RIVETED JOINTS - SHAN YiMeng; MI ShiQing; ZHOU Jian; XUAN ShanYong; HU JunShan (Jixie qiangdu)
The riveting process is a frequently utilized technique for joining components in aircraft assembly, but the complex damage and deformation of riveted joints may lead to intricate and unpredictable failure modes during the service phase. In order to thoroughly examine the deformation characteristics, mechanical properties and failure behavior of single-lap composite riveted joints, the three-dimensional Hashin failure criteria and exponential stiffness degradation method was used to establish an asymptotic damage prediction model for composite materials. Riveting forming and quasi-static tensile simulation were performed on riveted parts with different riveting process parameters, and the corresponding simulation results were compared with experimental results. The results indicate that the radial expansion of the rivet shank is non-uniform when subjected to pressure riveting force. Furthermore, the forming damage primarily transpires in the hole wall near the driven head, wherein the fibercrushing and interfacial shear cracks dominate. The uniformity of the hole expansion in the joint with a 4. 82 mm diameter is superior to that of a 4.9 mm diameter, resulting in better ultimate bearing strength. Moreover, the numerical model's displacement-load curve aptly reflects the trend and features of the actual mechanical properties. The predicted ultimate strength level is also comparable to the test results. Notably, the numerical model effectively captures the damage forms and range of fibers and matrix in the micro-morphology on the bearing plane, confirming the validity of the damage prediction model.